Peningkatan Mutu Pendidikan: Kajian Literatur Tentang Konsepsi Kualitas, Kualitas Sekolah dan Penyelenggaraan Lembaga Pendidikan - Afiefatuz Zakiyah; Cut Wima Umiana; Mu’alimin Mu’alimin; Khoirul Anwar (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Educational quality is a crucial aspect in the provision of education because it influences the quality of the human resources produced. However, studies on educational quality are still largely conducted in a partial manner, focusing on the concept of quality, the characteristics of quality schools, and the organization of educational institutions. This study aims to describe the concept of quality in educational quality, analyze the characteristics of quality schools, and examine the scope of educational institutions that contribute to improving educational quality. The study used a qualitative approach with a literature review method. The results of the study indicate that educational quality is a multidimensional concept encompassing the quality of educational inputs, processes, outputs, and outcomes. Quality schools are characterized by effective leadership, a strong culture of quality, high teacher quality, a conducive learning environment, and a sustainable quality assurance system. In addition, the organization of educational institutions oriented towards professional governance, stakeholder participation, and continuous evaluation has been shown to contribute to improving educational quality. This study contributes in the form of a conceptual synthesis that integrates the dimensions of educational quality, the characteristics of quality schools, and the organization of educational institutions within a comprehensive analytical framework.